Late Jurassic syn-rift deposition in the Flemish Pass basin, offshore Newfoundland: Evidence for Tithonian magmatism and Appalachian-Variscan sediment sources from quantitative mineral and detrital zircon U–Pb-Hf isotope studies of Mizzen discovery strata. (December 2022) - Beranek, Luke P.; Nissen, Adam; Murphy, Sandra; Grant, David; Goudie, Dylan; Oldham, Lindsay; Johns-Buss, Emily G.
Abstract: Quantitative mineral and detrital zircon U–Pb-Hf isotope studies of syn-rift sandstone units in the Mizzen F-09 delineation well, northern Flemish Pass basin, were conducted to test competing models for Grand Banks paleogeography and Late Jurassic development of the Newfoundland-Iberia magma-poor rift system. Bodhrán formation (informal nomenclature) strata yield ca. 145–155 Ma detrital zircon grain populations that indicate a late Tithonian (146 ± 1 Ma) maximum depositional age for syn-rift fluvial to tide-modulated fluvial strata in Mizzen F-09 and evidence for Grand Banks rift magmatism to have occurred throughout the Late Jurassic. Late Tithonian tectonic subsidence and magmatism in the northern Flemish Pass basin region were coincident with the onset of necking processes and extreme crustal thinning within the Newfoundland-Iberia rift system. The chondritic to superchondritic Hf isotope compositions of Late Jurassic detrital zircon grains indicate repeated partial melting of lithospheric mantle during rift development, perhaps along master detachment faults or transfer zone systems. Bodhrán formation strata have chemically unstable minerals (plagioclase, potassium feldspar, garnet, muscovite, rutile, staurolite) and late Paleozoic to Paleoarchean detrital zircon age populations that together show provenance from Appalachian-Variscan basement and cover assemblages. A positive correlation between the abundance of metamorphic minerals and unique-aged, mid-Permian (ca. 271–280 Ma) detrital zircon grains from post-Variscan igneous rocks indicate Iberian provenance contributions to Bodhrán formation strata. The new results from Mizzen F-09 are consistent with models for WNW-directed fluvial discharge into the northern Flemish Pass basin and sediment derivation from upper Paleozoic foreland basin or cover assemblages located west of Variscan front, some which may have been stripped off Beothuk Knoll, Flemish Cap, or adjacent highlands. Highlights: Tithonian strata in the Flemish Pass basin were deposited during syn-rift magmatism. Tithonian deposition was coeval with early necking and crustal breakup processes. Some metamorphic minerals and detrital zircon grains have Iberian provenance. WNW-directed Tithonian rivers had headwaters in Flemish Cap and Beothuk Knoll. Mizzen discovery and Terra Nova oil field have coeval, but unconnected river systems.